2021
DOI: 10.3389/fpls.2021.632708
|View full text |Cite
|
Sign up to set email alerts
|

A Composite Analysis of Flowering Time Regulation in Lettuce

Abstract: Plants undergo profound physiological changes when transitioning from vegetative to reproductive growth. These changes affect crop production, as in the case of leafy vegetables. Lettuce is one of the most valuable leafy vegetable crops in the world. Past genetic studies have identified multiple quantitative trait loci (QTLs) that affect the timing of the floral transition in lettuce. Extensive functional molecular studies in the model organism Arabidopsis provide the opportunity to transfer knowledge to lettu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 112 publications
(183 reference statements)
1
35
0
Order By: Relevance
“…However, the PVE values in the 2013 and 2014 experiments for dtf7.1 and dts7.1 differed. In a previous study, several flowering time QTLs on LG7 explained 11.2%, 30.23%, 39.6%, and 51.7% of the phenotypic variance in separate experiments that used the same mapping population (PI251246 × Salinas) [ 48 ]. It was suggested that the environment-sensitive QTLs represent genetic variations in the upstream signaling of the flowering time pathway, where environmental pressured are perceived and converted into molecular signals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the PVE values in the 2013 and 2014 experiments for dtf7.1 and dts7.1 differed. In a previous study, several flowering time QTLs on LG7 explained 11.2%, 30.23%, 39.6%, and 51.7% of the phenotypic variance in separate experiments that used the same mapping population (PI251246 × Salinas) [ 48 ]. It was suggested that the environment-sensitive QTLs represent genetic variations in the upstream signaling of the flowering time pathway, where environmental pressured are perceived and converted into molecular signals.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed bolting and flowering is preferred for vegetable production; however, over-late flowering is unfavorable for seed production [ 48 ]. The presence of CS alleles in dtb7.1 , and ln7.1 on LG7 increased the number of days to bolting and number of leaves.…”
Section: Discussionmentioning
confidence: 99%
“…QTL naming followed the nomenclature convention using q + trait abbreviation + chromosome number + QTL number on the particular chromosome. Trait abbreviations followed those suggested by Han et al 2021.…”
Section: Qtl Mapping and Model Selectionmentioning
confidence: 99%
“…The author later described four more Ef genes in additional crosses (Ryder and Milligan 2005). More recently, multiple quantitative trait loci (QTLs) for bolting and owering time, as well as for stem length, which correlates with earliness of bolting, have been identi ed on lettuce chromosomes 2 and 7 (Jeuken and Lindhout 2004;Hartman et al 2012Hartman et al , 2013Han et al 2021) in crosses between cultivated lettuce and its wild relatives. In a recombinant inbred line (RIL) population developed from crossing late and early bolting lettuce cultivars and evaluated in four summer experiments, three QTLs where identi ed on chromosomes 2, two QTLs on chromosome 5, and one each on chromosomes 7 and 8 (Jenni et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, multiple genetic mapping and association studies have reported genetic loci controlling bolting (Lavelle 2009;Jenni et al 2013;Mamo et al 2019;Sthapit Kandel et al 2020;Seki et al 2020) and flowering time traits in lettuce (Hartman et al 2012(Hartman et al , 2013aKwon et al 2013;Niroula 2017). A recent review on this topic reported a total of 64 quantitative trait loci (QTLs) associated with bolting and/or flowering time phenotypes in lettuce (Han et al 2021a). Two QTLs on Chromosomes 2 and 7, qFLT2.1 and qFLT7.1, have shown major effects on lettuce flowering time across multiple mapping populations.…”
Section: Introductionmentioning
confidence: 99%